Environmental vertical management reform and firms’ ESG performance: evidence from China - Jing Yang; Qiqi Wang; Yueyuan Huang (Humanities & Social Sciences Communications)
Abstract Understanding how policy adaptation influences firms’ shift toward sustainability is a crucial global issue. In response, this paper investigates the impact of China’s environmental vertical management reform (EVMR) on corporate environmental, social, and governance (ESG) performance. The reform aimed to address prior shortcomings by restructuring power allocation and redefining the authority and responsibility between local governments and environmental protection departments. Focusing on the micro perspective of firms, we employ a staggered difference-in-difference model to analyze a sample of A-share listed companies from 2009 to 2021. Our findings show that the new environmental reform significantly enhances the ESG performance of local firms. Three key underlying mechanisms are highlighted: the strengthening of provincial environmental regulatory capacity, intensified local environmental law enforcement, and increased corporate environmental compliance. Additionally, the lack of reform incentives and the differentiated implementation of provincial government are key constraints limiting the reform’s effectiveness. This study contributes to the theoretical understanding of government structural reform, emphasizing the critical role of institutional contexts in evaluating the balance between environmental decentralization and centralization. It also provides a detailed, contextual, and multi-tier analysis that enriches both grassroots governance theories and sustainability literature.